Benzyloxycalix[8]arene supported Pd–NHC cinnamyl complexes for Buchwald–Hartwig C–N cross-couplings. Issue 15 (29th June 2021) - Abi Fayssal, Sandra; Naret, Timothée; Huc, Vincent; Buendia, Julien; Martini, Cyril; Schulz, Emmanuelle
Abstract : The synthesis of a Pd–NHC cinnamyl-complex supported on a calix[8]arene and its use in Buchwald–Hartwig amination is reported. Thanks to the support, the products were isolated with low levels of residual palladium, in some cases below standards. Abstract : The scalable synthesis of Pd–NHC cinnamyl complexes supported on benzyloxycalix[8]arene is reported. These catalysts are very active for Buchwald–Hartwig cross-coupling reactions, allowing the coupling of aryl chlorides and bromides with a wide variety of alkyl and aryl amines using low catalytic loadings. The supported complexes also successfully afforded attractive unsymmetrical triarylamines, and in one case, promoted the synthesis of an unprecedented Pd-catalyzed C–H activation product. Thanks to the calixarenic support, the target products could be isolated with low levels of residual palladium, and in some cases, even below the restrictive toxic metal standards applied by the pharmaceutical industry. Through an easy to implement procedure, these perfectly characterised catalysts thus combine the best of homogeneous and heterogeneous catalysis: high efficiency (similar to or even better than the corresponding homogeneous complexes) and low Pd leaching levels expected from heterogeneous catalysts.